2022
DOI: 10.3390/ijerph19159682
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress among Frontline Physicians and Nurses in the Early Phase of COVID-19 Pandemic in Italy

Abstract: During the COVID-19 health emergency, healthcare professionals faced several ethical demanding job stressors, becoming at particular risk of moral distress. To date, only a few scales have been developed to evaluate moral distress among frontline professionals working in contact with COVID-19 patients. Moreover, although many healthcare professionals from various disciplines were converted to COVID-19 patient care, no study has yet analyzed whether the resulting change in duties might represent a risk factor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Interestingly, both doctors and nurses believe that MD is promoted by insufficient training to provide necessary treatment and support (35,7% and 30,6% respectively, Table 2) and that more training would alleviate the risk of MD (38,9% and 39,8% respectively, Table 3). Our data are supported by the Maffoni's results that showed that appropriate training decreased the levels of MD [4].…”
Section: Differences Between Doctors and Nursessupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, both doctors and nurses believe that MD is promoted by insufficient training to provide necessary treatment and support (35,7% and 30,6% respectively, Table 2) and that more training would alleviate the risk of MD (38,9% and 39,8% respectively, Table 3). Our data are supported by the Maffoni's results that showed that appropriate training decreased the levels of MD [4].…”
Section: Differences Between Doctors and Nursessupporting
confidence: 88%
“…In the early phase of the pandemic, it has been reported that doctors experienced higher levels of MD compared to the nurses [4]. This difference was explained by the inclusion of a cohort of doctors who had to perform tasks outside their usual range clinical duties (e.g., dermatologists and pediatricians redeployed to treat Covid-19 infected patients).…”
Section: Differences Between Doctors and Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the contingencies of the COVID-19 pandemic, which forced residents of nursing homes to remain in their own rooms [ 70 ]. Therefore, at the overall level, it seems that nurses adopted the pre-pandemic patterns of prioritisation (e.g., failing in ensuring fundamental care) with the intent of reducing exposure in patients’ rooms for an extended period and to avoid the source of contagion [ 71 ], and/or due to the fatigue caused by the personal protective equipment worn (e.g., [ 72 ]). The rationed nursing activities did not turn out to be very different from those of the pre-pandemic period (e.g., [ 2 , 73 ]), as also emerged in those studies that included comparative studies [ 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also investigate the role of personality traits that were found to be precursors of workaholism (e.g., neuroticism) [121]). More research is also needed to identify other personal and environmental resources (e.g., professional self-efficacy; managerial support) [122]) that could buffer the detrimental effects of technostress on workers' well-being. Moreover, selection bias cannot be ruled out because of the nonprobability convenience sampling strategy.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%